Near-Automatic Routine Field Calibration/Correction of Glider Salinity Data Using Whitespace Maximization Image Analysis of Theta/S Data - Allen, John T.; Munoz, Cristian; Gardiner, Jim; Reeve, Krissy A.; Alou-Font, Eva; Zarokanellos, Nikolaos (Frontiers in Marine Science, 2020)
Glider vehicles are now perhaps some of the most prolific providers of real-time and near real-time operational oceanographic data. However the data from these vehicles can and should be considered to have a long term legacy value capable of playing a critical role in understanding and separating inter-annual, inter-decadal and long term global change. To achieve this we have to go further than simply assuming the manufacturers calibrations; and field correct glider data in a more traditional way, for example, by careful comparison to water bottle calibrated lowered CTD datasets and/or ‘gold’ standard recent climatologies. In this manuscript we bring into the 21st century an historical technique that has been used manually by oceanographers for many years/decades for field correction, thermal lag correction and adjustment for biological fouling. The technique has now been made semi-automatic for machine processing of oceanographic glider data, although it’s future and indeed its origins have far wider scope. The subject of this manuscript is drawn from the original Description of Work (DoW) for a key task in the recently completed JERICO-NEXT (Joint European Research Infrastructure Network for Coastal observatories) EU funded program, but goes on to consider future application and the suitability for integration with machine learning.